Malaysian Government's Rejection of Rohingya Refugees - Jayanti, Nur; Sagena, Uni W. (LifeSciFi, 2024)
Malaysia, like most other Southeast Asian countries, has not signed the refugee convention and protocol and therefore asylum seekers and refugees are considered illegal immigrants by law, although the UNHCR provides assurances that refugees with UNHCR documents will not be arrested by the authorities. This research investigates the situation of Rohingya who are refugees in Malaysia, with a focus on the reasons why Malaysia rejects the increase in Rohingya refugee arrivals. The research method used is qualitative descriptive research using secondary data sources such as books, journals, news articles and other related information. The research results show that the general problems faced by Rohingya refugees in Malaysia include limited access to health services, education, as well as social and economic problems. Refugees face difficulties in obtaining health care due to financial problems and low health literacy. In the education sector, refugee children do not have access to formal academic institutions and rely on community learning centers. Economically, refugees experience difficulties in finding decent work. Nevertheless, the Malaysian government as a member of ASEAN has tried to care for refugees without sacrificing the welfare of its population.